Development of mass spectrometry-based carbene footprinting strategies for the study of protein structure and interactions - Manzi, Lucio (2017)
Protein interactions are crucial for the survival of living organisms. The possibility of mapping the contact surfaces between proteins and their interacting partners is fundamental to understanding the mechanisms involved in the process. For these reasons techniques able to provide structural information on a short time scale and employing small amounts of material are sought after. The work reported in this thesis explores the use of carbene-based labelling in combination with mass spectrometry for protein footprinting and its applications in the study of protein structure and interactions. Studies on the efficiency and selectivity of a novel water-soluble photo-activated probe revealed its superior properties in comparison with diazirine-based reagents previously described for the same application. Using this methodology, the contact surface of the complex between lysozyme and NAG5, a carbohydrate substrate, was accurately mapped. The same technique was successfully employed to shed light on the structural change occurring to USP5, a large multi-domain deubiquitinating enzyme, upon its binding to diubiquitin. The use of carbene footprinting in combination with other biophysical techniques allowed to characterise the spatial arrangement of domains located at a module junction in the large multi-modular gladiolin polyketide synthase paving the way for future efforts by synthetic biologists to hijack the chemistry of this antibiotic-producing multiprotein enzyme to produce novel active compounds. The possibility of using carbene-based footprinting to gain insight into the structure of integral membrane proteins was also explored. The probe introduced in this work exhibited peculiar labelling properties when activated in the presence of a detergent-solubilised membrane protein. The reagent selectively reacted with portion of the protein in contact with detergent molecules showing potential to elucidate the quaternary structure of multimeric membrane proteins.